Penggunaan Metode Read Aloud untuk Meningkatkan Kemampuan Berkomunikasi melalui Bacaan - Handini, Frida Dian; Siregar , Alfina Gustiany (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
In this era, many children have begun to leave the habit of reading because they are more interested in playing gadgets than reading books. The tendency to play gadgets has a negative impact on children's development in communicating. As we know, communication must be done in two directions while when children play gadgets there are no communication activities that take place. In the absence of two-way communication when children play gadgets can have an impact on decreasing children's ability to absorb information and communication skills. However, this is exacerbated by teachers and children's environment that has not been maximized in directing children to like reading. This is due to the lack of awareness of teachers or children's environment on the importance of reading and also the lack of availability of media that interests children to read. Departing from this problem, a team of lecturers and students of English Language Education Study Program at Quality University of Berastagi carried out community service by providing knowledge about reading methods that can attract children's interest in reading books, namely the Read Aloud method. Read aloud is one strategy of reading aloud with the aim of focusing children's attention. Read aloud can also make reading a fun activity so as to create information, build vocabulary, focus attention, stimulate questions so as to create discussion so that children can focus more on following the learning process. From the activities carried out at the Yayasan Nurul Hidayah for grade 3 students, they seemed enthusiastic about listening to the stories read by the speakers and from their friends and seemed to focus on listening, increasing vocabulary, and taking the essence of the stories read. Keywords: Communication Skills, Read Aloud Method, Students